Effect of Vitamin D Replacement on Insulin Sensitivity in Subjects With Vitamin D Deficiency. (1st December 2012) - Simha, Vinaya; Mahmood, Muhammad; Ansari, Mohammmed; Spellman, Craig W.; Shah, Pankaj
Abstract : Background and Objective: Low vitamin D levels correlate with measures of insulin resistance and prevalence of diabetes mellitus, but there are limited and conflicting data on changes in insulin resistance after vitamin D replacement. The objective of the current study was to examine whether vitamin D replacement improves insulin sensitivity. Methods: In this randomized double-blind placebo-controlled study, 12 healthy subjects with plasma 25-hydroxy vitamin D (25[OH]D) levels of less than 20 ng/mL were treated with ergocalciferol, 50, 000 units, orally once a week for 8 weeks or matching placebo. The main outcome measure was insulin-stimulated glucose infusion rate during the last 20 minutes of a hyperinsulinemic-euglycemic glucose clamp study. Results: At baseline, plasma 25(OH)D levels were similar between the ergocalciferol and placebo groups (13.3 ± 3.8 and 15.7 ± 2.4 ng/mL, respectively; P = 0.3) but were higher in the ergocalciferol group at 8 weeks (18.8 ± 5 vs 12.5 ± 2.2 ng/mL; P = 0.02). Glucose infusion rate was similar between the 2 groups both at baseline and after 8 weeks of treatment. Changes in plasma 25(OH)D levels did not correlate with change in glucose infusion rate. Conclusion: Administration of ergocalciferol, 50, 000 units, weekly for 8 weeks in subjects with low vitamin D levels improves 25(OH)D levels but does not improve insulin sensitivity.